The Historical and Contemporary Life-Value of the Canadian Labour Movement - Noonan, Jeff (Labour / Le Travail, 2013)
Neo-liberal ideology has attempted to set diﬀerent groups of workers— employed and unemployed, public and private sector, unionized and non-unionized—in opposition to each other. A successful response will require more than clear philosophical principles. It will require detailed, difficult, and long-term political eﬀorts to construct solidarity. At the same time, that practical political work requires principles. The most eﬀective principles on the basis of which solidarity can be built are those that disclose shared interests. The life-value principles underlying the most significant achievements of the union movement are the best means by which the shared interests of all workers can be disclosed.